A digital approach to international strategy development & distributor selection for SME’s and micro-firms. Case Study: NEEM Sunita Passi - Olafimihan, Jeti Oluwa (2016)
The purpose of this project was to research findings on SME and micro-firm internationalisation and to provide a framework that will guide strategy development and foreign partner selection. The findings were to be applied to a UK based skin and body care company - NEEM Sunta Passi (NSP), which faced international strategy development and implementation challenges.